172. THE MEDIASTINOSCOPIC RADICAL ESOPHAGECTOMY WITH A TRANS-BICERVICAL APPROACH USING INTRAOPERATIVE NERVE MONITORING (IOMN). (24th September 2022) - Tokairin, Yutaka; Nagai, Kagami; Shiobara, Hiroyuki; Ando, Masayuki
Abstract: We developed 'mediastinoscopic esophagectomy with lymph node dissection' (MELD), performed under pneumomediastinum via a trans-bicervical and transhiatal approach using cadavers. A clinical trial on the feasibility and safety of MELD showed it to be useful for complete mediastinal lymph node dissection. We report the indications and novel aspects of MELD. MELD was indicated for patients of thoracic esophageal cancer without bulky primary lesions or lymph node metastases. MELD was performed in 16 patients. First, 101R and part of the 106recR lymph nodes were dissected in open surgery. After attaching an APS electrode for intraoperative nerve monitoring (IOMN) to the right vagus nerve, open surgery was changed to the pneumomediastinal method. The dorsal side of the esophagus was dissected along the visceral sheath. The 106tbL lymph nodes and the106recR lymph nodes were dissected using a right trans-cervical pneumomediastinal approach. The 106recL lymph nodes were dissected using a left trans-cervical pneumomediastinal approach. The median pneumomediastinal operation time was 320 minutes. The median amount of bleeding was 230 mL, and the median postoperative hospital stay was 16 days. Regarding complications, eight patients developed recurrent laryngeal nerve palsy (right, n = 3; left, n = 2; bilateral, n = 3), but no patients required conversion to thoracotomy, and no leakage, pneumonia, or operative deaths occurred. After incorporating the use of IOMN, the incidence of recurrent laryngeal nerve palsy was drastically reduced recurrent laryngeal nerve palsy was drastically decrease. Previous clinical trials shown that MELD can retrieve the mediastinal lymph nodes at the same level as thoracoscopic esophagectomy. The incidence of recurrent laryngeal nerve palsy was reduced by IONM; thus, MELD is considered a feasible procedure for radical esophagectomy.